Enhanced light interception and light use efficiency explain overyielding in young tree communities. (3rd March 2021) - Williams, Laura J.; Butler, Ethan E.; Cavender‐Bares, Jeannine; Stefanski, Artur; Rice, Karen E.; Messier, Christian; Paquette, Alain; Reich, Peter B.
Abstract: Diverse plant communities are often more productive than mono‐specific ones. Several possible mechanisms underlie this phenomenon but their relative importance remains unknown. Here we investigated whether light interception alone or in combination with light use efficiency (LUE) of dominant and subordinate species explained greater productivity of mixtures relative to monocultures (i.e. overyielding) in 108 young experimental tree communities. We found mixed‐species communities that intercepted more light than their corresponding monocultures had 84% probability of overyielding. Enhanced LUE, which arose via several pathways, also mattered: the probability of overyielding was 71% when, in a mixture, species with higher 'inherent' LUE (i.e. LUE in monoculture) intercepted more light than species with lower LUE; 94% when dominant species increased their LUE in mixture; and 79% when subordinate species increased their LUE. Our results suggest that greater light interception and greater LUE, generated by inter and intraspecific variation, together drive overyielding in mixed‐species forests. Abstract : Diverse plant communities are often more productive than mono‐specific ones. Several possible mechanisms underlie this phenomenon but their relative importance remains unknown. Here, we quantify the relative contributions of a suite of light‐related mechanisms to diversity‐enhanced productivity in young experimental tree communities. Our results suggest that greater light interception and greater light use efficiency, generated by inter and intraspecific variation, together drive overyielding in mixed‐species forests.